(untitled) (REMUNOM, 2025)
This study aimed to evaluate the antioxidant activity and characterize the chemical constituents of the hydroalcoholic extract of Acmella oleracea (jambu), with a focus on the different parts of the plant. The analysis was conducted using electrospray ionization mass spectrometry (ESI-MS) in both positive and negative ionization modes, along with the DPPH free radical scavenging assay to assess antioxidant activity. The results showed that the stem extract exhibited the highest antioxidant capacity among the parts analyzed, with significantly lower EC₅₀ values (0.03 µg/mL) compared to the standard (gallic acid – 3.3 µg/mL), indicating strong efficacy in neutralizing free radicals. Antioxidant activity decreased proportionally with concentration, with the stem maintaining superior performance across all tested levels. Mass spectrometry revealed a wide diversity of secondary metabolites. In positive ion mode, glycosylated flavonoids were predominant, including kaempferol 3-rutinoside-7-glucoside (m/z 753), kaempferol 3-rutinoside-7-arabinose (m/z 711), kaempferol 3-methoxy-7-O-glucoside (m/z 475), and kaempferol 3-O-arabinose-7-methoxy (m/z 433), in addition to free kaempferol (m/z 287). The ion at m/z 391 was attributed to derivatives of alkylamides or oxygenated terpenoids. In negative mode, highly polar compounds were detected, such as hydrolyzable tannins (m/z 787), conjugated phenolic acids (m/z 577), glycosylated flavonoids (m/z 751), ellagic acid derivatives (m/z 709), and modified triterpenoids (m/z 563), all known for their bioactive properties. These findings reinforce the pharmacological potential of jambu as a natural source of antioxidants, with promising applications in the pharmaceutical, cosmetic, and nutraceutical industries.